Optimalisasi Peran Sukuk sebagai Instrumen Investasi Syariah dalam Mendorong Pembangunan Ekonomi Nasional - Romadhoni, Desy Dwi; Ramidah, Nur; Damayanti, Ramdhani Kartika (Diponegoro Journal of Islamic Economics and Business, 2022)
In recent years, Sukuk have become more popular . With a fairly large number of 163 series or 29% of the total series of sovereign bonds, it is no wonder that sukuk have developed and can be used to improve financial aspect in the capital market through a sharia-compliant structure. And it is undeniable that it can also help national economic development if its role is implemented properly. This article will discuss the role of sukuk in promoting national economic growth and development. This includes the development of sukuk as a sharia investment instrument in Indonesia as well as the strategies implemented to optimize the role of sukuk to encourage national economic development. This article is presented in a descriptive-analytic manner using a qualitative approach through the literature study method.